Biodegradable Food Packaging Innovations and Implications for Sustainable Food Systems (Journal of Agriculture and Biology, 2025)
The application of conventional plastic food packaging has skyrocketed over the last couple of decades, necessitating a shift towards biodegradable options for the continued sustainability of food systems. The researchers look into putative solutions for bio-polimer food packaging using biological, biotechnological and computer science-oriented methods. The use of certain natural bio-polymers such as cellulose, chitosan or starches offer some form of package, which is environmentally friendly as it enhances food and safety while also serving as a barrier to microbial invasion. Innovations in biotechnology, such as the microbial synthesis of polyhydroxyalkanoates (PHA) and the synthesis of polylactic acid (PLA), improve the industrial applicability and the functional characteristics of the biodegradable food packaging. Strategies using informatics like artificial intelligence for material and design optimization, and block-chain technology for supply chain tracking further enhance the practicality of maybe sustainable packaging. The ramifications of the biodegradable food package go beyond the benefits to the environment; they range from enhanced food safety, decreased leaching of harmful substances, to prolonging shelf-life of the goods. No single solution exists for managing the costs, performances, and practical industrial requirements, which calls for more active policies and cooperative scientific research. The researchers encourage different domains of innovation to collaborate to complete the outlined objectives directed toward shaping the food systems and the environment.